Feasibility and safety of orbital atherectomy for the treatment of in‐stent restenosis secondary to stent under‐expansion. Issue 1 (26th January 2020) - Neupane, Saroj; Basir, Mir; Tan, Christina; Sultan, Adnan; Tabaku, Mishel; Alqarqaz, Mohammad; Khandelwal, Akshay; Gupta, Ankur; Don, Creighton; Alaswad, Khaldoon
Abstract: Background: Debulking and ablative techniques are sometimes used for the treatment of in‐stent restenosis (ISR) secondary to resistant stent under‐expansion (SU). The safety and effectiveness of orbital atherectomy (OA) in this cohort of patients has not been reported. Methods: We retrospectively evaluated consecutive patients treated with OA for ISR secondary to balloon undilatable SU at two academic tertiary care centers between October 2016 and June 2019. Angiographic or intravascular imaging identified SU. Technical success was defined as residual 0% stenosis with TIMI III flow. Results: A total of 41 patients were included in the study. Patients had an average age of 65 ± 12 years; 73% male, 61% diabetic, 41% with prior coronary artery bypass grafting, 61% with a prior incident of ISR, 51% presented with stable angina, 17% unstable angina, and 32% non‐ST elevation myocardial infarction (MI). Implantation of the under‐expanded stents occurred between 2 months and 22 years prior to the index procedure. A total of 27% of patients had multiple layers of stents in the target lesion and 32% of patients had in‐stent chronic total occlusion. Technical success was achieved in 40 (98%) patients. There were 2 (5%) major adverse cardiovascular events; both of them were periprocedural MI from the no‐reflow phenomenon. There were 2 (5%) Ellis type II coronary perforations that required no intervention. Conclusions: OA can be effectively performed as an adjunctive tool in the treatment of ISR with balloon undilatable SU. The use of OA for SU is not approved by the U.S. Food and Drug Administration and is "off label" and caution must be used to limit any device/stent interaction.